Zwei weitere neue Blattlausarten aus Norddeutschland und ein neues Genus (Homoptera: Aphididae). - Müller, Fritz Paul (Contributions to Entomology = Beiträge zur Entomologie, 1958)
Spatulophorus nov. gen. morphologically resembles to some extend Myzaphis Buckton. But there are good characters for the distinction of the two genera. The genotype, S. incanae n. sp., lives apparently only on Berteroa incana. The other described aphid, Aulacorthum flavum n. sp., occurs on Vaccinium uliginosum and being transferable on some other Ericaceae. It is nearest related to A. vaccinii H. R. L., but the abdominal tergum of the apterous viviparous females is colourless. Besides this a few other characters for separation are recorded.Nomenclatural ActsSpatulophorus Müller, 1958 (Aphididae), gen. n.flavum Müller, 1958 (Aulacorthum), spec. n.incanae Müller, 1958 (Spatulophorus), spec. n.